Nano-Coating of Chitosan Incorporated with Cinnamomum Zeylanicum Es sential Oil: Application on Chicken Sausages for Quality Enhancement and Shelf-Life Extension - Shreya Rao, Neelagiri; Shukla, V H; Zende, R J; Vaidya, V M; Ingole, S D (Journal of Meat Science, 2026)
The application of edible coatings containing nanoemulsions of essential oil is a growing area of research for quality enhancement of meat and meat products using natural preservation methods. The present work was done to evaluate the quality and shelf-life of chicken sausages coated with an edible coating of nanoemulsions of chitosan and cinnamon essential oil. A total of four types of edible coatings were prepared, viz. T1: 0.3 % chitosan only; T2: 0.3% chitosan and 0.3% cinnamon essential oil; T3: nanoemulsion of 0.3% chitosan; T4: nanoemulsion of 0.3% chitosan incorporated with 0.3% cinnamon essential oil. The edible coatings were characterized and chicken sausages were coated with the developed edible coatings while determining the quality and shelf-life at regular intervals during refrigeration storage.: UV-Vis spectrophotometry, particle size analysis, and HR-TEM analysis revealed the spherical-shaped nanoparticles in the 50-200 nm range. Edible coatings significantly (P<0.05) improved the microbiological and physicochemical quality parameters and oxidative changes in T4 than other treatments throughout the refrigeration storage (4±1°C). Hunter color values were significantly (P<0.05) improved in T4 compared to other treatments during storage. No sensory discrimination was observed upon applying nano-emulsions over chicken sausages throughout the storage period. The application of the nanoemulsions coating extended the shelf-life by 10-15 days in T4 than control during refrigeration storage.